Spatial distribution and genetic diversity of TYLCV in Saudi Arabia: TYLCV Diversity in KSA - Iqbal, Zafar (Cellular and Molecular Biology, 2025)
This study investigated the genetic diversity, phylogeny, and evolutionary dynamics of Tomato yellow leaf curl virus (TYLCV) across seven regions in Saudi Arabia. Analyzing 28 full-length TYLCV genomes, phylogenetic analysis revealed two distinct clades: one predominantly comprised of isolates from the Ahsa (Eastern province) region and the other encompassing isolates from Northern and Western regions. The Ahsa region exhibited significantly higher TYLCV prevalence and genetic diversity, harboring the most divergent isolates with high haplotype (Hd = 1.00) and nucleotide (π = 0.079) diversity. Conversely, regions like Jeddah and Hadasham showed lower diversity, suggesting less or stable viral populations. Genetic diversity analyses revealed high variation in coding regions like CP and Rep, which are under strong selective pressures and prone to recombination. Conversely, V2 displayed lower diversity, indicating purifying selection. Selection pressure analysis using dN/dS ratios indicated diversifying selection in C4 (2.20) and Rep (1.28). Single Likelihood Ancestor Counting identified one positively selected site in Rep. In contrast, Fast Unconstrained Bayesian AppRoximation identified multiple sites in C4 (8), TrAP (7), REn (6), and V2 (1), suggesting roles in host adaptation and immune evasion. A total of 32 credible recombination events, predominantly in Ahsa isolates, were identified using RDP and confirmed by GARD analysis. These events, involving both inter- and intraspecies recombination, play a crucial role in enhancing TYLCV genetic diversity and adaptability. The conservation of motifs in V2 and C4 indicated their essential roles in TYLCV function. In contrast, variations in ORFs like CP, Rep, TrAP, and REn among specific isolates may promote viral diversity and adaptation. This study demonstrates the crucial role of geographic and genetic factors, with Ahsa as a key hub for TYLCV diversity, in driving viral evolution and diversification. The findings emphasize the need to monitor regions with high viral diversity, like Ahsa, and develop strategies to manage TYLCV's swift spread.